Alluvium and empire : the archaeology of colonial resettlement and indigenous persistence on Peru's north coast - VanValkenburgh, Parker (Archaeology of indigenous-colonial interactions in the Americas, 2021)
"Alluvium and Empire examines the archaeology of Indigenous communities and landscapes that were subject to Spanish colonial forced resettlement during the sixteenth century. Written at the intersections of history and archaeology, the book critiques previous approaches to the study of empire and models a genealogical approach that attends to the open-ended-and often unpredictable-ways in which empires take shape."--
Keywords: Indians of South America : Peru : Lambayeque (Department) : Antiquities